Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1176/appi.ps.57.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Psychiatric Care With Representative Payeeship for Persons With Serious Mental Illness

Abstract: Use of a coordinated representative payee program was found to be effective in improving outcomes at 12 months. Although this evidence supports the wider implementation of a coordinated representative payee program, only 31 percent of the experimental group had their money banked with a representative payee. Therefore, future studies should focus on achieving a better understanding of the causal components of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…A randomized controlled trial assessed the impact of representative payee services on housing, quality of life, substance use, and depressive symptoms. This study demonstrated positive trends in the reduction of homelessness, as well as statistically significant decreases in money mismanagement and increases in quality of life (Conrad et al, 2006). Research shows that having a representative payee decreases hospitalizations and improves treatment compliance (Luchins et al, 2003).…”
Section: Introductionmentioning
confidence: 75%
“…A randomized controlled trial assessed the impact of representative payee services on housing, quality of life, substance use, and depressive symptoms. This study demonstrated positive trends in the reduction of homelessness, as well as statistically significant decreases in money mismanagement and increases in quality of life (Conrad et al, 2006). Research shows that having a representative payee decreases hospitalizations and improves treatment compliance (Luchins et al, 2003).…”
Section: Introductionmentioning
confidence: 75%
“…The ability to create a circle of care by helping clients cultivate relationships with other professionals is viewed as an asset in programs that support individuals in crises (Conrad et al, 2006;Joy et al, 2007;Malla et al, 2003;Tierney & Kane, 2011). It was found that for CMS a circle of care refers to helping clients with all elements of their life, essentially encircling them with support so that they can be successful in crisis resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with mental illness are sometimes unable to meet their basic needs, as illustrated in the present study. They can be subject to increased financial victimization and might have difficulty managing their money (Conrad et al;. In turn, financial troubles can result in poor credit ratings, which can contribute to difficulty in securing rental applications (Luchins, Roberts, & Hanrahan, 2003) and…”
Section: Discussionmentioning
confidence: 99%
“…The impact of assigning a formal representative payee largely depends on the payee assigned, with wide variability in payee practices (31). The literature suggests that representative payee programs, particularly when coordinated with other psychiatric treatment, are beneficial (16, 32, 33). …”
Section: Discussionmentioning
confidence: 99%